DAYA DUKUNG PAKAN GAJAH SUMATERA (Elephasmaximus sumatranus Temminck.) DI TAMAN NASIONAL TESSO NILO PROVINSI RIAU - Sugi Ari Wardana; Defri Yoza; Yossi Oktorini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The sumatran elephant is rare animals wich spreadin almost all parts of sumatera island. The conflict between people with the sumatran elephants often occurred in the forest area alongside people settlement. The large amount of sumatran elephants population in Tesso Nilo National Park highly dependent on the carrying capacity of the habitat and the available feed. This research aims to know populationof sumatran elephants and carrying capacity of feedthe sumatran elephantin the area of Tesso Nilo National Park Province of Riau. The studywas usedthe method purposive sampling by determined the position of elephant on the track, determinationof sample plot offeed location the sumatran elephants and carrying capacity collected of feed the sumatran elephant. Data obtained areComposition Vegetation (species density, species frequency, species dominance), IndexValue Important (IVI), Species Diversity, Biomass Feed, CarryingCapacity of Feed and Carrying Capacity of habitat. The result of interviews with the mahout in the village Lubuk Kembang Bunga, there are 2 groups the sumatran elephants with the total as many 38 tail. The results of the research showed that the availability of feed in 1 Hectare areasin a Tesso Nilo National Park were not sufficient to 1 tail sumatran elephants.The carrying capacity of habitat sumatran elephant wich exists at Tesso Nilo National Park regional with broad area 1331.19 Hectare can not accommodate for sumatran elephants. Keywords: elephant, location, population, feed.